Microstructure, Anisotropy and Formability Evolution of an Annealed Aisi 430 Stainless Steel Sheet - Iquilio-Abarzua, R; Castro-Cerda, F; Hernandez-Duran, E (John Wiley and Sons Inc, 2022)
The effect of the microstructure on the principal strain paths (uniaxial, plane, and biaxial) in the formability processes of ferritic stainless steel AISI 430 sheets is studied. The Marciniak test (determination of the plastic strain of sheet metal with a flat tip punch) is applied to determine the forming limit curves and different strain levels in the strain paths by the digital image correlation technique. The formability is discussed in light of the microstructure, standard mechanical properties, work hardening behavior, and anisotropy measurements (R-value). Electron backscatter diffraction analysis is carried out to determine the texture of the selected strain paths. The texture evolution shows a marked γ (<111>// normal direction [ND]) fiber and cube ({001} <100>) texture component under the biaxial strain mode, whereas the α (<110>// rolling direction [RD]) fiber is somewhat favored under uniaxial plane strain. The results are compared with texture simulations performed under the fully constrained Taylor model, finding reasonable agreement with the experimentally measured main components. © 2021 Wiley-VCH GmbH